Oolong tea attenuates neuroinflammation by modulating the microbiota-gut-brain axis in a rat model of autism - Zheng, Peng; Zhao, Hongbo; Zhang, Xingliang; Wu, Qiuting; Zheng, Zhen; Liu, Shaoqun (Frontiers in Nutrition, 2025)
BackgroundAutism spectrum disorder (ASD) is a prevalent neurodevelopmental disorder with limited effective treatments. Emerging evidence implicates dysregulation of the microbiota-gut-brain axis in ASD pathogenesis. Oolong tea (OT), a traditional Chinese tea with neuroprotective properties, may modulate this axis, but its effects and mechanisms in ASD remain unclear. We investigated whether OT attenuates neuroinflammation in a valproic acid (VPA)-induced rat model of autism through the microbiota-gut-brain axis and the TLR-4/IκB-α/NF-κB signaling pathway.MethodsAn ASD model was established by prenatal VPA exposure (500 mg/kg, i.p., E12.5). Postnatal VPA-treated rats received OT (100, 200, or 400 mg/kg/day) for 4 weeks. Behavioral assessments included self-grooming, marble burying, and three-chamber social interaction tests. Nissl staining evaluated neuropathology. Gut microbiota composition was analyzed using 16S rRNA sequencing of fecal samples. Lipopolysaccharide (LPS), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) levels were measured in the plasma, intestine, and brain using enzyme-linked immunosorbent assay. Intestinal and blood-brain barrier (BBB) integrity (claudin-1/5, occludin, ZO-1) and TLR-4/IκB-α/NF-κB pathway activation were assessed by Western blot/immunofluorescence. Microglial (Iba-1) and astrocytic (GFAP) activation and neuronal TLR-4 localization (co-staining with Neun) were examined. Antibiotic cocktail (ABX)-induced microbiota depletion validated gut microbiota dependency.ResultsOT (400 mg/kg/day) significantly ameliorated repetitive behaviors (reduced self-grooming duration and marble burying), sociability deficits (improved sociability/social preference index), and attenuated cortical neuronal loss in VPA-treated rats. OT restored gut microbiota dysbiosis, specifically reducing pathogenic Ruminococcaceae and Bacteroides abundances. It decreased LPS, IL-6, and TNF-α levels in the plasma, intestine, and cortex, while enhancing intestinal and BBB tight junction protein expression. OT suppressed TLR-4/IκB-α/NF-κB activation in both intestine and cortex, with TLR-4 predominantly localized to neurons, and reduced microglial/astrocytic activation. Critically, ABX treatment abolished OT’s neuroprotective effects and restored neuroinflammation.ConclusionOT attenuates ASD-like phenotypes and neuroinflammation in VPA-treated rats by rebalancing gut microbiota, restoring intestinal/BBB barriers, and inhibiting neuronal TLR-4/IκB-α/NF-κB signaling. This study highlights OT’s potential as a microbiota-targeted therapeutic strategy for ASD.